Multiple description image and video coding for P2P transmissions - Quaresma, Marisa Raposo (2015)
Peer-to-Peer (P2P) media streaming is, nowadays, a very attractive topic due to the bandwidth available to serve demanding content scales. A key challenge, however, is making content distribution robust to peer transience. Multiple description coding (MDC) has, indeed, proven to be very effective with problems concerning the packets’ losses, since it generates several descriptions and may reconstruct the original information with any number of descriptions that may reach the decoder. Therefore multiple descriptions may be effective for robust peer-to-peer media streaming. In this dissertation, it will not only be showed that, but also that varying the redundancy level of description on the fly may lead to a better performance than the one obtained without varying this parameter. Besides that, it is shown, as well, that varying the Bitrate on the fly outperforms the redundancy on it. Furthermore, the redundancy and the Bitrate were varied simultaneously. Thus, it is shown that this variation is more efficient when the packet loss is high. The experiments reported above were done using an experimental test bed developed for this purpose at the NMCG lab of the University of Beira Interior. It was also used the REGPROT, a video encoder developed by our research team, to splitted the video into multiple descriptions, which were, later, distributed among the peers in the test bed. After the request of the client, the referred encoder decoded the descriptions as they were being received.